A single upper limb pose estimation method based on the improved stacked hourglass network - Peng, Gang; Zheng, Yuezhi; Li, Jianfeng; Yang, Jin (Zielona Góra: Uniwersytet Zielonogórski)
At present, most high-accuracy single-person pose estimation methods have high computational complexity and insufficient real-time performance due to the complex structure of the network model. However, a single-person pose estimation method with high real-time performance also needs to improve its accuracy due to the simple structure of the network model. It is currently difficult to achieve both high accuracy and real-time performance in single-person pose estimation.
Keywords: convolutional neural networks; stacked hourglass network; skeleton key point; single upper limb pose estimation; human?machine coordination